Costs and benefits of accepting presidential term limits: "should I stay or should I go?". Issue 1 (2nd January 2022) - Fruhstorfer, Anna; Hudson, Alexander
ABSTRACT: As presidents approach the end of their constitutionally defined term in office, they face a number of difficulties, most importantly the deprivation of sources of power, personal enrichment, and protection from prosecution. This leads many of them to attempt to circumvent their term limits. Recent studies explain both the reasons for the extension or full abolition of term limits, and failed attempts to do so. Key explanations include electoral competition and the post-term fate of previous post holders. What we do not know yet is how compliance with term limits may be tied to the current president's expectations for their post-term fate. In particular, we do not know whether leaders who attempt to remove term limits and fail to do so jeopardize their post-term career as a result, and conversely, whether leaders who comply will have better outcomes in terms of security, prestige, and economic gain. Hence, we ask how the decision of a leader to comply or not comply with term limits is conditioned by the expectation of their post-term fate. To address this question, this article introduces new data on the career trajectories of term-limited presidents and its systematic effect on term limit compliance.